Reversible Electroporation–Mediated Liposomal Doxorubicin Delivery to Tumors Can Be Monitored With Zr-Labeled Reporter Nanoparticles - Govindarajan Srimathveeravalli PhD; Dalya Abdel-Atti BS; Carlos Pérez-Medina PhD; Haruyuki Takaki MD, PhD; Stephen B. Solomon MD; Willem J. M. Mulder PhD; Thomas Reiner PhD (Molecular Imaging, 2018)
Reversible electroporation (RE) can facilitate nanoparticle delivery to tumors through direct transfection and from changes in vascular permeability. We investigated a radiolabeled liposomal nanoparticle ( 89 Zr-NRep) for monitoring RE-mediated liposomal doxorubicin (DOX) delivery in mouse tumors. Intravenously delivered 89 Zr-NRep allowed positron emission tomography imaging of electroporation-mediated nanoparticle uptake. The relative order of 89 Zr-NRep injection and electroporation did not result in significantly different overall tumor uptake, suggesting direct transfection and vascular permeability can independently mediate deposition of 89 Zr-NRep in tumors. 89 Zr-NRep and DOX uptake correlated well in both electroporated and control tumors at all experimental time points. Electroporation accelerated 89 Zr-NRep and DOX deposition into tumors and increased DOX dosing. Reversible electroporation–related vascular effects seem to play an important role in nanoparticle delivery to tumors and drug uptake can be quantified with 89 Zr-NRep.